Creep and thermal cracking of ultra-high volume fly ash mass concrete at early age. (May 2019) - Zhao, Zhifang; Wang, Kejin; Lange, David A.; Zhou, Hougui; Wang, Weilun; Zhu, Dongming
Abstract: An experimental study characterized fresh and hardened ultra-high volume fly ash mass concrete (HP-HVFA, with 80% fly ash and a water-to-binder ratio of 0.26) and normal content fly ash mass concrete (NS-FA, with 35% fly ash and a water-to-binder ratio of 0.43). The creep and thermal cracking behaviors of the HP-HVFA and NS-FA concrete were evaluated using a temperature stress testing machine (TSTM). A series of TSTM tests were conducted under an adiabatic curing mode and a temperature matched curing (TMC) mode. The results indicate that HP-HVFA concrete had moderate strength at early age and desirable fresh and hardened engineering properties. Under the both curing modes studied, HP-HVFA exhibited lower hydration temperature rise. Under the TMC mode, both compressive and tensile creep of HP-HVFA were lower than that of NS-FA although their specific creep and creep-to-shrinkage strain ratio at time of cracking were almost the same. Under adiabatic mode, HP-HVFA had higher creep strain, specific creep, and creep-to-shrinkage strain ratio than NS-FA.